Faktor-Faktor Ideal Perusahaan Dalam Pelaksanaan CSR (Corporate Social Responsibity) - Herman Herman; Riky Novarizal (UIR PRESS, 2017)
Corporate social responsibility (CSR) is an act that the company does to the public ingeneral in the context of empowerment. The main actors involved in the implementationof this CSR is all stakeholders who work in sync for the sustainable development. Theimplementation of CSR has many aspects, such as sustainable development in theframework of community empowerment. For the smooth implementation of CSR isnecessary some of the factors that support the implementation of CSR namely Buildinghuman capital, Strengthening economics, Assessing social cohesion, Encouraginggovernance, Protecting the environment, Two ways.